Combining computer-mediated communication with data-driven instruction: EFL learners' pragmatic development of compliment responses. (December 2021) - Zhang, Ying
Abstract: The use of computer-mediated communication (CMC) combined with data-driven instruction to facilitate second/foreign language (L2) pragmatic development has been shown to be promising. Despite increasing amounts of CMC-based interventional studies of L2 pragmatics, existing literature is inconclusive concerning the influence of CMC paired with data-driven instruction on L2 pragmatic competence. Moreover, few studies have incorporated qualitative analyses exploring factors that affect L2 learners' pragmatic decision-making. Thus, this mixed-methods study aimed to further investigate the effect of CMC on English as a Foreign Language (EFL) learners' pragmatic development of compliment responses (CRs) in two conditions: CMC by itself and CMC combined with data-driven instruction. Fifty-nine university-level Chinese EFL students were divided into two groups; the experimental group engaged in CMC with native speakers and received data-driven instruction in CRs, whereas the control group had CMC without data-driven instruction. Results revealed that the experimental group outperformed the control group in the immediate and delayed post-intervention tests regarding appropriateness and variety, indicating a positive and durable effect of CMC coupled with data-driven instruction on L2 pragmatic development. Additionally, findings from retrospective interviews showed that L2 pragmatic knowledge, crosslinguistic influence, and online processing load potentially influence L2 pragmatic choices. Implications for instructors are discussed.